Mental health and conflict: a pilot of an online eye movement desensitisation and reprocessing (EMDR) intervention for forcibly displaced Syrian women - Aseel Hamid; Amanda C. de C. Williams; Muslihah Albakri; Katrina Scior; Sian Morgan; Hamodi Kayal; Matthew Wilcockson; Rouba Drouish Alkaja; Rouba Drouish Alkaja; Sahbaa Alsayed; Sahbaa Alsayed; Robin Logie; et al. (Frontiers Media S.A., 2024)
BackgroundThe Syrian conflict has been ongoing since 2011. Practical and scalable solutions are urgently needed to meet an increase in need for specialised psychological support for post-traumatic stress disorder given limited availability of clinicians. Training forcibly displaced Syrians with a mental health background to remotely deliver specialised interventions increases the availability of evidence based psychological support. Little is known about the effectiveness of online therapy for forcibly displaced Syrian women provided by forcibly displaced Syrian women therapists.PurposeTo pilot an evidence-based trauma therapy, Eye Movement Desensitisation and Reprocessing (EMDR), carried out online by trained forcibly displaced Syrian women therapists for forcibly displaced Syrian women who require treatment for post-traumatic stress disorder (PTSD).Methods83 forcibly displaced Syrian women, living in Türkiye or inside Syria, with diagnosable PTSD, were offered up to 12 sessions of online EMDR over a period of 3 months. This was delivered by forcibly displaced Syrian women therapists who were trained in EMDR. Data were gathered, using Arabic versions, on PTSD symptoms using the Impact of Events Scale Revised, depression symptoms using the Patient Health Questionnaire-9 and anxiety symptoms using the Generalised Anxiety Disorder Assessment-7 at baseline, mid-point, and end of therapy.ResultsPTSD scores, depression scores and anxiety scores all significantly reduced over the course of treatment, with lower scores at midpoint than baseline and lower scores at end of treatment than at midpoint. Only one participant (1%) exceeded the cutoff point for PTSD, and 13 (16%) exceeded the cutoff points for anxiety and depression at the end of treatment.ConclusionIn this pilot study up to 12 sessions of online EMDR were associated with reductions in PTSD, anxiety and depression symptoms in Syrian women affected by the Syrian conflict. The training of forcibly displaced Syrian mental health professionals to deliver online therapy is a relatively low cost, scalable, sustainable solution to ensure that those who are affected by the conflict can access specialised support. Further research is needed using a control group to confirm that the observed effects are due to EMDR treatment, as is research with post-treatment follow-up to ascertain that benefits are maintained.